Composite resin composition and composite resin molded article
By using the combination of main agent resin, low molecular weight resin and compatibilizer in composite resin, combined with high shear stress kneading treatment, the problem of insufficient mechanical strength of general plastics is solved, and fluidity, formability and exudation inhibition is achieved. , improves the performance of composite resin molded bodies and is suitable for the replacement of engineering plastics and metal materials.
Patent Information
- Application Number
- CN202380042262.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-05-15
- Publication Date
- 2024-12-20
AI Technical Summary
General plastics have shortcomings in mechanical strength, fluidity and formability, resulting in limited application scope. At the same time, engineering plastics do not have ideal solutions due to high prices and high environmental burden.
The composite resin composition containing the main agent resin, low molecular weight resin and compatibilizer is adopted, and the fiber length and particle-like filler ratio are controlled by premix and melt-kneading with the fibrous filler, and mixed with high shear stress , a composite resin molded body with bimodal molecular weight peak is formed.
It realizes the maintenance of fluidity and formability under high concentration fillers, inhibits leakage, and improves the mechanical strength and appearance quality of composite resin molded bodies, which is suitable for the replacement of engineering plastics and metal materials.
Smart Images

Figure CN119173589A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite resin composition which is excellent in fluidity and moldability and can suppress appearance defects such as bleeding of a molded body, and a composite resin molded body which is a molded body including the composite resin composition. Background Art
[0002] So-called "general-purpose plastics" such as polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyvinyl chloride (PVC) are not only very cheap, but also easy to shape, and are only a fraction of the weight of metals or ceramics. Therefore, general-purpose plastics are widely used as materials for a wide variety of daily necessities such as bags, various packages, various containers, and sheets, as well as for industrial parts such as automobile parts and electrical parts, home appliances, construction products, and daily necessities and sundry goods.
[0003] However, general-purpose plastics have disadvantages such as insufficient mechanical strength. Therefore, the reality is that general-purpose plastics do not have sufficient properties required for materials used in various industrial products such as mechanical products such as automobiles and electrical, electronic, and information products, and their application range is limited.
[0004] On the other hand, so-called "engineering plastics" such as polycarbonate, fluororesin, acrylic resin, and polyamide have excellent mechanical properties and are used in various industrial products such as automobiles and other mechanical products, as well as electrical, electronic, and information products. However, engineering plastics have the problems of high prices, difficulty in recycling monomers, and high environmental burden.
[0005] Therefore, it is expected to significantly improve the material properties (mechanical strength, etc.) of general-purpose plastics. For the purpose of strengthening general-purpose plastics, it is known that natural fibers, glass fibers, carbon fibers, etc. as fibrous fillers are dispersed in the resin of general-purpose plastics to improve the mechanical strength of the general-purpose plastics. In addition, it is also known that inorganic powders such as talc and silica, pulp powders, waste paper powders, cellulose powders such as sawdust, etc. as particulate fillers are dispersed in the resin of general-purpose plastics to improve the mechanical strength of the general-purpose plastics. Among them, organic fillers such as cellulose are inexpensive and have excellent environmental properties during production and disposal, so they have attracted attention as reinforcing materials.
[0006] Although the mechanical strength is improved by dispersing fillers in the resin, on the other hand, fillers are entangled in the composite resin, which deteriorates the fluidity and the moldability. In addition, the higher the concentration of fillers and the longer the fibers, the more entanglement occurs and the worse the fluidity.
[0007] In order to improve the fluidity of filler-dispersed plastics, various companies have conducted research. Patent document 1 provides a molded body, in which 0.5% to 17.5% of wax is added to a cellulose composite polyethylene containing 10% to 70% cellulose powder and 25% to 89% polyethylene to improve the fluidity, thereby improving the surface roughness of the molded body.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 3167020 Summary of the invention
[0011] However, in Patent Document 1, wax is used to improve fluidity, and since wax is uniformly dispersed in the resin, fluidity is improved, but there is a problem of wax precipitating and seeping out onto the surface of the molded body. In addition, there is also a problem of reduced strength.
[0012] The present application is an invention for solving the above-mentioned conventional problems, and an object thereof is to provide a composite resin composition which suppresses a decrease in fluidity even when a filler is added at a high concentration, suppresses the occurrence of bleed-out, has high strength, and has good appearance.
[0013] In order to achieve the above-mentioned purpose, the composite resin composition of the present application comprises a main resin, a low molecular weight resin, a compatibilizer and a filler. The low molecular weight resin is a resin of the same type as the main resin, the molecular weight of the low molecular weight resin is lower than the molecular weight of the main resin, and the compatibilizer has a molecular structure substantially the same as the molecular structure of the main resin.
[0014] According to the composite resin composition of the present application, a composite resin molded body that has both fluidity and strength and can suppress the occurrence of bleed-out can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic cross-sectional view showing the cross-sectional structure of the composite resin molded body according to the first embodiment.
[0016] Figure 2 This is an enlarged schematic cross-sectional view of the composite resin molded body according to the first embodiment.
[0017] Figure 3A This is a schematic diagram of a fibrous filler as a constituent member of the composite resin molded body according to the first embodiment.
[0018] Figure 3B yes Figure 3A A partial enlarged view of the inclusion end of the fibrous filler.
[0019] Figure 4This is an electron microscope image of the fibrous filler in the composite resin molded body of the first embodiment.
[0020] Figure 5 It is a schematic diagram of the manufacturing process of the composite resin molded body of Embodiment 1.
[0021] Figure 6 Table 1 shows the measurement results of Examples 1 to 5 and Comparative Examples 1 to 7. DETAILED DESCRIPTION
[0022] The composite resin composition of the first embodiment includes a main resin, a low molecular weight resin, a compatibilizer, and a filler. The low molecular weight resin is a low molecular weight body of the same type of resin as the main resin, and the compatibilizer has substantially the same molecular structure as the main resin.
[0023] The composite resin composition of the second embodiment may be the composite resin composition of the first embodiment, wherein the compatibilizer in the composite resin composition is a graft polymer of a resin having substantially the same molecular structure as the main resin.
[0024] The composite resin composition of the third embodiment may be: in the above-mentioned first or second embodiment, the number average molecular weight Mnk of the main resin in the composite resin composition is 10 times or more and less than 500 times the number average molecular weight Mnt of the low molecular weight resin, and the molecular weight peak of the composite resin composition is bimodal.
[0025] The composite resin composition of a fourth embodiment may be a structure in which, in any one of the first to third embodiments, more low molecular weight resin and compatibilizer exist around the fibrous filler than in the main resin, and the main resin exists at the periphery thereof.
[0026] The composite resin composition of the fifth embodiment is: in any one of the first to fourth embodiments above, the filler in the composite resin composition includes a fibrous filler and a particulate filler having a smaller aspect ratio than the fibrous filler, the aspect ratio of the fibrous filler is greater than 10, the aspect ratio of the particulate filler is less than 2, the proportion of the fibrous filler is greater than 1wt% and less than 10wt%, and the proportion of the particulate filler among the above fillers is greater than 50wt% and less than 70wt%.
[0027] The composite resin composition of the sixth embodiment may be: in any one of the above-mentioned embodiments 1 to 5, only the ends of the fibrous filler in the composite resin composition in the fiber length direction are defibrated, and the concentration of the low molecular weight resin around the portion with an increased surface area after defibration is greater than the concentration of the low molecular weight resin around the central portion in the fiber length direction which is not defibrated.
[0028] A composite resin composition according to a seventh aspect may be the composite resin composition according to any one of the first to sixth aspects, wherein the filler is a natural material containing cellulose.
[0029] An eighth aspect of the composite resin composition may be any one of the first to seventh aspects, wherein in any one of the first to eighth aspects, the main component resin is an olefin resin.
[0030] A composite resin molded article according to a ninth aspect is a molded article comprising the composite resin composition according to any one of the first to eighth aspects.
[0031] Hereinafter, a composite resin composition and a composite resin molded body according to an embodiment will be described with reference to the drawings. In the following description, the same reference numerals are used for the same components, and the description thereof will be appropriately omitted.
[0032] (Implementation method 1)
[0033] <Composite resin composition and molded article>
[0034] Figure 1 This is a schematic cross-sectional view showing the cross-sectional structure of a composite resin molded body 10 which is a molded body formed of the composite resin composition according to the first embodiment. Figure 2 This is an enlarged schematic cross-sectional view of the composite resin molded body 10 according to the first embodiment.
[0035] The composite resin composition of the first embodiment contains a melt-kneaded product including a main resin, a filler, a low molecular weight resin, and an additive. Figure 1 and Figure 2 As shown in the schematic cross-sectional view of FIG. 1 , at least a fibrous filler 2, a particulate filler 3, a low molecular weight resin 4, and a compatibilizer as an additive are mixed and dispersed in a main resin 1.
[0036] <Main resin>
[0037] In the present embodiment 1, in order to ensure good formability, the main resin 1 is preferably a thermoplastic resin. As thermoplastic resins, olefin resins such as polyethylene and polypropylene (including cyclic olefin resins), styrene resins, (meth) acrylic resins, organic acid vinyl ester resins or their derivatives, vinyl ether resins, halogen-containing resins, polycarbonate resins, polyester resins, polyamide resins, thermoplastic polyurethane resins, polysulfone resins (polyethersulfone, polysulfone, etc.), polyphenylene ether resins (polymers of 2,6-xylenol, etc.), cellulose derivatives (cellulose esters, cellulose carbamates, cellulose ethers, etc.), lignin resins, modified lignin resins, silicone resins (polydimethylsiloxane, polymethylphenylsiloxane, etc.), rubbers or elastomers (diene rubbers such as polybutadiene and polyisoprene, styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylic rubbers, polyurethane rubbers, silicone rubbers, etc.), engineering plastics, etc. The above resins can be derived from petroleum, plants, or microorganisms. In addition, the above-mentioned resin can also be a recycled resin that is reprocessed from a resin that has been formed once, and the recycling method can include material recycling, chemical recycling, and the like. The above-mentioned resin can be used alone or in combination of two or more. In addition, it can have decomposability based on microorganisms, water, heat, etc. It should be noted that the main component resin 1 only needs to have thermoplasticity and is not limited to the above-mentioned materials.
[0038] Among these thermoplastic resins, the main resin 1 is preferably an olefin resin or a polyamide resin having a relatively low melting point. As an olefin resin, in addition to homopolymers of olefin monomers, copolymers of olefin monomers and copolymers of olefin monomers and other copolymerizable monomers are also included. As olefin monomers, for example, chain olefins (ethylene, propylene, 1-butene, isobutylene, 1-pentene, 4-methyl-1-pentene, 1-octene and other α-C2-20 olefins, etc.), cyclic olefins, etc. can be cited. These olefin monomers can be used alone or in combination of two or more. Among the above-mentioned olefin monomers, chain olefins such as ethylene and propylene are preferred. As other copolymerizable monomers, for example, fatty acid vinyl esters such as vinyl acetate and vinyl propionate; (meth) acrylic acid monomers such as (meth) acrylic acid, (meth) acrylic acid alkyl esters, and (meth) acrylic acid glycidyl ester; unsaturated dicarboxylic acids or their anhydrides such as maleic acid, fumaric acid, and maleic anhydride; vinyl esters of carboxylic acids (such as vinyl acetate, vinyl propionate, etc.); cyclic olefins such as norbornene and cyclopentadiene; and dienes such as butadiene and isoprene. These copolymerizable monomers can be used alone or in combination of two or more. As specific examples of olefin resins, copolymers of chain olefins (especially α-C2-4 olefins) such as polyethylene (low-density, medium-density, high-density or linear low-density polyethylene, etc.), polypropylene, ethylene-propylene copolymers, ethylene-propylene-butene-1 and other terpolymers can be cited. Examples of polyamide resins that are polymers formed by bonding a plurality of monomers via amide bonds include nylon (polyamide) 6, nylon 11, nylon 12, nylon 66, nylon 610, nylon 612, nylon 1010, nylon 1012, and nylon 6T.
[0039] <Additives>
[0040] The following is an explanation of the additives. The composite resin composition and the molded body of the present embodiment 1 may contain additives for the purpose of improving the adhesion between the fibrous filler 2 and the main resin 1, or the dispersibility of the fibrous filler 2 in the main resin 1. As additives, various titanate coupling agents, silane coupling agents, unsaturated carboxylic acids, maleic acid, maleic anhydride, or modified polyolefins obtained by grafting the anhydride, fatty acids, fatty acid metal salts, fatty acid esters, etc. can be cited. The above-mentioned silane coupling agent is preferably an unsaturated hydrocarbon-based or epoxy-based silane coupling agent. There is no problem even if the surface of the additive is treated with a thermosetting or thermoplastic polymer component for modification. The additive of the present embodiment is preferably an additive obtained by grafting hydrophilic groups such as maleic anhydride on the polymer as described above, and it is further preferred that the polymer of the additive is a resin (compatibilizer) having a molecular structure substantially the same as that of the main resin 1.
[0041] <Fiber-like filler>
[0042] Figure 3A This is a schematic diagram of a fibrous filler 2 which is a constituent member of the composite resin molded body according to the first embodiment. Figure 3B yes Figure 3A A partial enlarged view of the fibrous filler 2 including the end 5 . Figure 4 (a) is an electron microscope image of a fibrous filler in the composite resin molded body of Embodiment 1, and (b) is an electron microscope photograph of a part of an end portion of the fibrous filler in (a) which is partially enlarged.
[0043] The fibrous filler 2 is described. Among the fibrous fillers, there are also particulate fillers whose diameter is roughly the same as the fiber length. The particulate filler is basically the same material as the fibrous filler 2, and only the filler length and aspect ratio are different. Therefore, the fibrous filler 2 is described in detail in the following description. The fibrous filler 2 (hereinafter sometimes referred to as "fiber") contained in the composite resin composition and the molded body of the present embodiment is mainly used in the composite resin molded body molded using the composite resin composition for the purpose of improving mechanical properties, improving dimensional stability by reducing the linear expansion coefficient, etc. For this purpose, the fibrous filler 2 preferably has a higher elastic modulus than the main resin 1, and specifically includes carbon fiber, carbon nanotube, pulp, cellulose, cellulose nanofiber, wood cellulose, wood cellulose nanofiber, basic magnesium sulfate fiber (basic magnesium sulfate fiber), potassium titanate fiber, aluminum borate fiber, calcium silicate fiber, calcium carbonate fiber, silicon carbide fiber, wollastonite, xonotlite, various metal fibers, natural fibers such as cotton, silk, wool or hemp, regenerated fibers such as jute fiber, rayon or cuprammonium fiber, semi-synthetic fibers such as acetate and Promix, synthetic fibers such as polyester, polyacrylonitrile, polyamide, aramid, polyolefin, and modified fibers obtained by chemically modifying their surfaces and ends, etc. It may be needle-shaped instead of fibrous, and may be wood powder, bark, coffee, wheat, tea leaves, etc. extracted from fir, cypress, bamboo, reed, etc. In addition, among them, carbon and cellulose are particularly preferred from the viewpoint of availability, high elastic modulus and environmental friendliness. In addition, from the viewpoint of a recycling-oriented society, natural fibers such as cellulose and wood flour, natural materials, and waste materials extracted therefrom are preferred.
[0044] The shapes of the fibrous filler and the particulate filler are described below. In the case of natural fibers and natural materials, the starting materials of the fibrous filler and the particulate filler are the same, and the particulate filler is pulverized more finely to form particles. Figure 3A The symbol L in is the length of the fibrous filler or the particulate filler (hereinafter sometimes referred to as "fiber length"). Figure 3BThe symbol d in is the width of the fibrous filler or particulate filler (hereinafter sometimes referred to as "fiber diameter"). For fibrous fillers and particulate fillers, if there are many fibers with a large aspect ratio (L / d), that is, if there are many fibrous fillers, the elastic modulus increases. The aspect ratio of the fibrous filler is preferably greater than 10. However, if there are many fibers with a large aspect ratio, the fiber entanglement increases, and the fluidity and formability deteriorate. On the other hand, if there are many fibers with a small aspect ratio, that is, if there are many particulate fillers, the fluidity improves, the fiber agglomerates are less, and the appearance is also good. The aspect ratio of the particulate filler is preferably less than 2. However, if there are many fibers with a small aspect ratio, that is, if there are many particulate fillers, the elastic modulus decreases.
[0045] The ratio of the fibrous filler in the filler is, for example, 1 wt % to 10 wt % inclusive, and the ratio of the particulate filler in the filler is, for example, 50 wt % to 70 wt % inclusive.
[0046] The following describes additives. Additives are used to improve fluidity, and examples include wax, plasticizer, internal additives, external additives, etc. If they are not compatible with the main resin, cracks are likely to form between the main resin and the main resin, and there is a case where they become the starting point of cracks. Therefore, as additives, low molecular weight forms of the main resin are preferred.
[0047] <Main component resin and low molecular weight body (low molecular weight resin)>
[0048] If the molecular weight values of the main resin and the low molecular weight resin are too close, there is no effect of improving the fluidity of the main resin. If the values differ too much, it is easy to ooze out after molding. The appropriate molecular weight range is calculated by experiment and simulation. Preferably, the number average molecular weight Mnk of the main resin is 10 to 500 times the number average molecular weight Mnt of the low molecular weight resin. In addition, it is preferred that the molecular weight peak of the composite resin composition and the molded body is not a wide single-peak waveform, but exists as a double-peak waveform of the peak of the main resin and the peak of the low molecular weight body. In this way, the strength of the composite resin and the fluidity during molding can be taken into account.
[0049] The state of the resin and fibrous filler in the composite resin composition and the molded body is described. If the low molecular weight resin is dispersed in the composite resin, it will cause strength reduction and exudation at the same time. By performing the premixing described later, the low molecular weight resin is present in large quantities around the fibrous filler and the particulate filler, forming a structure in which the main resin exists on its periphery. The low molecular weight resin covers the particulate filler, thereby suppressing the deterioration of fluidity caused by the entanglement of the fiber. In addition, stress is easily concentrated on the interface between the filler and the main resin, but by the presence of a soft low molecular weight resin, stress can be relieved and strength can be improved. In addition, by the presence of the main resin on the outside of the low molecular weight resin, the low molecular weight resin that is easy to ooze out will not appear on the outside, so it is not easy to ooze out for the molded body.
[0050] like Figure 3B and Figure 4 As shown in (b), regarding the fibrous filler 2, the most preferred structure is that the defibration section 6 in the fiber length direction is partially defibrated. By defibration, a large amount of low molecular weight resin 4 can be entangled and present around. The defibration section 6 represents the defibration site. The shape of the optimal fiber is calculated as shown below based on the results of experiments and simulations. As the defibration section 6, it is preferred that it is more than 5% and less than 30% of the fiber length L of the entire fibrous filler 2. If the defibration section 6 is less than 5% of the entire fiber length L, the specific surface area is small, so a large amount of low molecular weight resin cannot be present. If it is more than 30%, the resin thickens and the fluidity deteriorates.
[0051] As the strength of the composite resin molded body, the relationship between the aspect ratio and the elastic modulus is described. When stress is applied to the composite resin molded body, if there are fibers with a large aspect ratio, even if the resin is elongated, the fibers with high rigidity are not easy to elongate, so the composite resin will not deform. As a result, the elastic modulus is improved. On the other hand, in the case of fibers with a small aspect ratio, the deformation suppression effect brought by the fibers when stress is applied is small, and the composite resin is deformed and the elastic modulus is reduced.
[0052] The relationship between the aspect ratio and the impact resistance is described. When an impact is applied to a composite resin molded body, if there are fibers with a large aspect ratio, the fibers cannot follow the elongation of the resin, and cracks are formed between the resin and the fibers. The cracks become the starting point and develop into ruptures. On the other hand, in the case of fibers with a small aspect ratio, since the fibers are thin, when an impact is applied, the fibers follow the elongation of the resin, and cracks are not easily formed, and rupture is not easy.
[0053] In order to further improve the mechanical properties, since the elastic modulus will be improved when there are many bonding interfaces between the fibrous filler and the main resin, it is preferred that the specific surface area of the fibrous filler is large. Figure 3B and Figure 4 As shown in the figure, a structure is formed in which at least one end portion in the longitudinal direction of one fiber is partially defibrated.
[0054] Below, the characteristic of fibrous filler 2 is described. About the kind of main agent resin 1 and fibrous filler 2, as mentioned above, if fibrous filler 2 is too soft relative to main agent resin 1, that is, the elastic modulus is low, then the elastic modulus of composite resin molding as a whole becomes low, and the result is strength reduction. On the other hand, if fibrous filler 2 is too hard relative to main agent resin 1, that is, the elastic modulus is high, then the shock wave generated during impact can not be propagated, but is absorbed at the interface of main agent resin 1 and fibrous filler 2, and therefore is easy to produce cracking and crack near this interface, and the result is that impact resistance decreases. Therefore, about the relationship between the elastic modulus of main agent resin 1 and fibrous filler 2, the elastic modulus of preferred fibrous filler 2 is high, and its difference is as small as possible. The best relationship can be calculated according to the simulation result, and the elastic modulus difference of preferred main agent resin 1 and fibrous filler 2 is within 20GPa.
[0055] In addition, these fibrous fillers 2 may be surface-treated with various titanate coupling agents, silane coupling agents, unsaturated carboxylic acids, maleic acid, maleic anhydride, or modified polyolefins grafted with the anhydride, fatty acids, fatty acid metal salts, fatty acid esters, etc., for the purpose of improving adhesion to the main resin 1 or dispersibility in the composite resin molded body. Alternatively, there is no problem even if the surface of the fibrous filler is treated with a thermosetting or thermoplastic polymer component.
[0056] <Method for producing composite resin molded article>
[0057] Next, a method for producing the composite resin molded body will be described. Figure 5 This is a flow chart illustrating the manufacturing process of the composite resin molded body of the present embodiment 1. Before being put into the melt-kneading treatment device, the fibrous filler including the particulate filler is pre-mixed with the powdery or liquid low molecular weight resin (low molecular weight body). No heating is performed during the pre-mixing, and the mixing is performed using a mixer, a stirrer, etc. As a result, the low molecular weight resin enters the fluffed part of the fiber of the fibrous filler. Thereafter, it is put into the melt-kneading treatment device (kneading device) together with the main resin, a compatibilizer, etc., and other additives are added as needed, and melt-kneaded in the device. As a result, the main resin, the low molecular weight resin, the additives, etc. are melted, and the fibrous filler, etc. are dispersed in the melted main resin, etc. In addition, the shearing action of the device is simultaneously used to promote the defibration of the agglomerated mass of the fibrous filler, so that the fibrous filler can be finely dispersed in the main resin.
[0058] In the past, as fibrous fillers and particulate fillers, fillers whose fibers were previously defibrated by pretreatment such as wet dispersion were used. However, if the fibrous filler is previously defibrated in a solvent used in wet dispersion, it is easier to defibrate than to defibrate in a molten main resin, so it is difficult to defibrate only the end portion and make the entire fibrous filler defibrated. In addition, the addition of pretreatment increases the number of steps and there is a problem of poor productivity.
[0059] In contrast, in the manufacturing process of the composite resin molded body of the present embodiment, a pre-treatment based on wet dispersion for the purpose of defibration and modification of fibrous fillers and particulate fillers is not performed, but melt-kneading treatment (complete dry process) is performed together with a main resin, additives, etc. In this process, a wet dispersion treatment of the fibrous filler is not performed, so that the fibrous filler can be partially defibrated only at the end as described above, and the number of steps is reduced, so that productivity can be improved.
[0060] In order to make the fiber of the present embodiment in the full dry process, it is preferred to apply high shear stress during mixing. As specific mixing methods, single screw mixer, twin screw mixer, roll mixer, Banbury mixer and their combination etc. can be cited. From the viewpoint that it is easy to apply high shear and mass production is also high, continuous twin screw mixer and continuous roll mixer are particularly preferred. As long as it is a method that can apply high shear stress, mixing methods other than the above can also be used.
[0061] The composite resin composition extruded from the melt kneading device is formed into a pellet shape by a cutting process such as a granulator. As a method of granulation, there are air heat cutting method, underwater heat cutting method, strand cutting method, etc., which are carried out immediately after the resin is melted. Alternatively, there is a pulverization method such as first forming a molded body or a sheet and then pulverizing and cutting.
[0062] The pellets as the composite resin composition are melted and injection molded in a mold to produce an injection molded product as a composite resin molded body. The fibrous filler and the particulate filler in the pellets are mixed as described above to obtain an injection molded product with excellent antibacterial properties, strength and appearance.
[0063] Hereinafter, each Example and each Comparative Example in the experiment performed by the inventors will be described.
[0064] (Example 1)
[0065] A pulp-dispersed polypropylene composite resin molded body was produced by the following production method.
[0066] Use conifer pulp (trade name: NBKP Celgar manufactured by Mitsubishi Paper Industries, Ltd.) as the starting material for fibrous fillers and particulate fillers. The conifer pulp is crushed by a pulverizer to obtain a mixture of fibrous fillers and particulate fillers. The aspect ratio and the surface area due to fluffing are adjusted by a pulverization process. The mixture of the fibrous filler and the particulate filler and the low molecular weight polypropylene (trade name: VISCOL 550-P manufactured by Sanyo Chemical Industries, Ltd.) as an additive are weighed in a weight ratio of 55:5 and dry mixed using a mixer. Thereafter, polypropylene (trade name: J108M manufactured by Prime Polymer Co., Ltd.) as the main resin, maleic anhydride-modified polypropylene (trade name: Umex manufactured by Sanyo Chemical Industries, Ltd.) as an additive, and the mixture of the fibrous filler and the additive are weighed in a weight ratio of 38:2:60 and dry mixed. Thereafter, melt-kneading and dispersion were performed using a twin-screw kneading machine (KRC kneader manufactured by Kurimoto Iron Works Co., Ltd.). The shear force can be changed by changing the screw structure of the twin-screw kneading machine, and the medium shear type specification was set in Example 1. The resin melt was hot-cut to produce pulp-dispersed polypropylene particles as a composite resin composition.
[0067] The prepared pulp-dispersed polypropylene particles were used to prepare a test piece of a composite resin molded body using an injection molding machine (180AD manufactured by Nippon Steel Works). The test piece preparation conditions were set to a resin temperature of 210°C, a mold temperature of 60°C, an injection speed of 60 mm / s, and a holding pressure of 80 MPa. The shape of the test piece was changed according to the evaluation items described below, and a dumbbell of size 1 was prepared to measure the elastic modulus. The test piece of the obtained pulp-dispersed polypropylene composite resin molded body was evaluated using the following method.
[0068] (Aspect ratio of fiber, end fiberization)
[0069] The obtained pulp dispersed polypropylene particles were immersed in a xylene solvent to dissolve the polypropylene, and the shape of the remaining pulp fibers was observed using SEM. About 50 representative fibers were measured at 5 locations, and the results showed that the average proportion of fibers with an aspect ratio of more than 10 was 7.5%, the average proportion of fibers with an aspect ratio of less than 2 was 55%, and the rest were fibers with an aspect ratio greater than 2 and less than 10. Fillers with an aspect ratio of more than 10 were set as fibrous fillers, and fillers with an aspect ratio of less than 2 were set as particulate fillers. In addition, the ends of the fibers were in a defibrated state, and the average value of the proportion of the defibrated portion within the length of one fiber was 23%.
[0070] (Liquidity)
[0071] In order to evaluate the fluidity of the obtained pulp-dispersed polypropylene particles, the melt viscosity was measured using a melt viscometer (manufactured by Toyo Seiki Seisaku-sho, Ltd., trade name: Capillograph F-1). The melt viscosity was measured in the range of shear rate of 12 to 2430 [1 / sec]. The melt viscosity at a shear rate of 1220 [1 / sec] was about 250 [Pa·s].
[0072] (Formability)
[0073] In order to evaluate the moldability of the obtained pulp-dispersed polypropylene particles, they were molded into dumbbell-shaped bodies with a thickness of about 1 mm, and whether they could flow to the ends and be molded was evaluated. It was confirmed that they could be molded to the ends.
[0074] (Precipitation on the surface of the molded body)
[0075] The obtained dumbbell of size 1 was placed in a high temperature and high humidity environment of 40°C and 85% for 1 week, and then the surface of the molded body was analyzed to determine whether the low molecular weight resin was precipitated. The surface analysis was performed by gel permeation chromatography. According to the results of gel permeation chromatography, it was confirmed that the low molecular weight resin was not observed from the surface of the molded body and did not ooze to the surface.
[0076] (Elastic modulus of composite resin molded body)
[0077] A bending test was performed using the obtained dumbbell-shaped test piece No. 1. The bending elastic modulus was 4.3 GPa, and the reinforcing effect of the filler was observed.
[0078] (Appearance of composite resin molded article)
[0079] The composite resin molded body was evaluated for appearance at the visual level. When there was no color unevenness or browning and the appearance was uniform, it was rated as OK, and when there was color unevenness or browning, it was rated as NG. This sample had an OK appearance.
[0080] (Example 2)
[0081] In Example 2, a low shear type kneader was used to prevent the fibers from being defibrated. The other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polypropylene pellets and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0082] (Example 3)
[0083] In Example 3, the number of passes through the kneader was set to 7 times the normal number to perform fiber defibration. The other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polypropylene particles and composite resin molded bodies. The same evaluation as in Example 1 was also performed.
[0084] (Example 4)
[0085] In Example 4, the pulp concentration was changed to 70%, and the material conditions and process conditions other than that were the same as those in Example 1 to produce pulp-dispersed polypropylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0086] (Example 5)
[0087] In Example 5, the main resin was polyethylene with a number average molecular weight of 200,000, the low molecular weight resin was polyethylene with a number average molecular weight of 2,000, and the compatibilizer was acid-modified polyethylene. The other material conditions and process conditions were the same as those in Example 1, and pulp-dispersed polyethylene particles and composite resin molded bodies were produced. The same evaluation as in Example 1 was also performed.
[0088] (Comparative Example 1)
[0089] In Comparative Example 1, the mixture of the fibrous filler and the particulate filler and the low molecular weight polypropylene as an additive were not pre-mixed by a mixer, but the polypropylene of the main resin and the additive were mixed simultaneously, and the material conditions and process conditions other than this were the same as those in Example 1 to produce pulp-dispersed polyethylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0090] (Comparative Example 2)
[0091] In Comparative Example 2, the low molecular weight polypropylene as an additive was set to polypropylene with a number average molecular weight of 200, and the other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polyethylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0092] (Comparative Example 3)
[0093] In Comparative Example 3, the low molecular weight polypropylene as an additive was set to polypropylene with a number average molecular weight of 20,000, and the other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polyethylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0094] (Comparative Example 4)
[0095] In Comparative Example 4, the starting material of pulp was changed to powdered cellulose, and the material conditions and process conditions other than that were the same as those in Example 1 to produce pulp-dispersed polypropylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0096] (Comparative Example 5)
[0097] In Comparative Example 5, pulp was not pulverized, and the other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polypropylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0098] (Comparative Example 6)
[0099] In Comparative Example 6, low molecular weight polypropylene was not added as an additive, and the other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polyethylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0100] (Comparative Example 7)
[0101] In Comparative Example 7, no compatibilizer was added, and the other material conditions and process conditions were the same as those in Example 1 to produce pulp-dispersed polyethylene particles and a composite resin molded body. The same evaluation as in Example 1 was also performed.
[0102] The measurement results in each of Examples 1 to 5 and Comparative Examples 1 to 7 are shown in Figure 6 In Table 1.
[0103] from Figure 6 Table 1 clearly shows that in Example 2, in which the fiber end defibration degree is set to 0% using a low shear type mixer, the force holding the low molecular weight resin around the fiber is slightly weak, and although no obvious oozing is observed, surface precipitation (oozing) can be slightly observed, resulting in a slightly poor appearance. It is confirmed that if a fibrous filler and a particulate filler with an aspect ratio smaller than that of the fibrous filler are included, the aspect ratio of the fibrous filler is 10 or more, and the aspect ratio of the particulate filler is 2 or less, and a low molecular weight resin of the same resin type as the main resin is pre-mixed with the fibrous filler as an additive, and its number average molecular weight is 10 to 500 times that of the main resin, and the molecular weight peak of the composite resin molded body is bimodal, then a composite resin molded body with excellent fluidity and moldability and poor appearance such as oozing of the molded body can be obtained.
[0104] In Example 3, in which the fiber was defibrated by setting the number of passes through the kneading machine to 7 times the normal number, a considerable number of fibers in the composite resin molded body were defibrated, and the end defibration degree reached 60%. As a result, the low molecular weight resin was retained around the fibers, and a molded body without bleeding was obtained, but the result was a low elastic modulus.
[0105] In Example 4 in which the pulp concentration was changed to 70%, the melt viscosity became slightly higher due to the increase in fiber concentration, and molding was slightly difficult. However, a composite resin molded body with poor appearance such as oozing of the molded body suppressed was obtained.
[0106] In Example 5 in which the main resin and the low molecular weight resin were set to polyethylene, compared with Example 1 using polypropylene, it was confirmed that as the resin type changed, the overall elastic modulus decreased, the melt viscosity increased, and it was slightly difficult to form. However, a composite resin molded body with poor appearance such as bleeding of the molded body was obtained.
[0107] In Comparative Example 1 in which no premixing was performed, the low molecular weight resin was not present in large amounts around the fibers, and oozing of the low molecular weight resin was observed on the surface, resulting in an NG appearance.
[0108] In Comparative Example 2, in which the low molecular weight polypropylene was set to a polypropylene with a number average molecular weight of 200, since the molecular weight was too small compared to the main resin, it was incompatible and bleed-out of the low molecular weight resin was observed on the surface, resulting in NG appearance.
[0109] In Comparative Example 3 in which the low molecular weight polypropylene was set to a polypropylene with a number average molecular weight of 20,000, no bleeding was observed, but the melt viscosity was high, and the effect of improving fluidity due to the low molecular weight resin was not observed. The moldability was poor, and the molded body did not flow to the end, resulting in an NG appearance.
[0110] In Comparative Example 4, in which the starting material of the pulp was changed to powdered cellulose, the proportion of the fibrous filler was 0% and the proportion of the particulate filler was 100%. As a result, the low molecular weight resin could not be held around the fibers, and the low molecular weight resin was observed to bleed out on the surface, resulting in an NG appearance. In addition, the reinforcing effect of the fibrous filler was reduced, resulting in a low elastic modulus.
[0111] In Comparative Example 5, where the pulp was not pulverized, the proportion of the fibrous filler was 100% and the proportion of the particulate filler was 0%. As a result, the elastic modulus was slightly higher, but the melt viscosity was higher, the moldability was poor, and the molded body did not flow to the end, resulting in an NG appearance.
[0112] In Comparative Example 6 in which no low molecular weight resin was added, the melt viscosity became high, the moldability was poor, and the molded product did not flow to the edge, resulting in an NG appearance.
[0113] In Comparative Example 7 in which no compatibilizer was added, the dispersibility of the fibrous filler in the main resin was insufficient, and the elastic modulus was as low as 2.9 GPa.
[0114] According to the above evaluation, it is confirmed that if a composite resin molded body contains a fibrous filler and a particulate filler having a smaller aspect ratio than the fibrous filler, the aspect ratio of the fibrous filler is greater than 10, and the aspect ratio of the particulate filler is less than 2, and a low molecular weight resin of the same resin type as the main resin is pre-mixed with the fibrous filler as an additive, and its number average molecular weight is 10 to 500 times that of the main resin, and the molecular weight peak of the composite resin molded body is a bimodal, then a composite resin molded body with excellent fluidity and moldability and capable of suppressing poor appearance such as bleeding of the molded body can be obtained.
[0115] It should be noted that the present application includes the case where any of the various embodiments and / or examples described above are appropriately combined to exert the effects of the various embodiments and / or examples.
[0116] Industrial Applicability
[0117] The composite resin molded body of the present application can provide a composite resin molded body that improves fluidity, can also suppress exudation, and has excellent mechanical strength compared to conventional general-purpose resins. By using the present application, the properties of the main resin can be improved, so it can be used as a substitute for engineering plastics or a substitute for metal materials. Therefore, the manufacturing cost of various industrial products made of engineering plastics or metals, or daily necessities can be greatly reduced. In addition, it can be applied to daily necessities, home appliance housings, building materials, automotive components, etc.
[0118] Description of Reference Numerals
[0119] 1 Main resin, 2 Fibrous filler (filler), 3 Granular filler (filler), 4 Low molecular weight resin, 5 End, 6 Defibrination part.
Claims
1. A composite resin composition comprising a main resin, a low molecular weight resin, a compatibilizer and a filler, The low molecular weight resin is the same type of resin as the main resin, The molecular weight of the low molecular weight resin is lower than the molecular weight of the main resin. The compatibilizer has a molecular structure substantially the same as that of the main resin.
2. The composite resin composition according to claim 1, wherein The compatibilizer is a graft polymer of a resin having a molecular structure substantially the same as that of the main resin.
3. The composite resin composition according to claim 1, wherein The number average molecular weight Mnk of the main resin is greater than or equal to 10 times and less than 500 times the number average molecular weight Mnt of the low molecular weight resin. The composite resin composition has two molecular weight peaks.
4. The composite resin composition according to claim 1, wherein The low molecular weight resin and the compatibilizer are present in larger amounts around the filler than in the main resin.
5. The composite resin composition according to claim 1, wherein The filler includes a fibrous filler having an aspect ratio of 10 or more and a particulate filler having an aspect ratio of 2 or less, The proportion of the fibrous filler in the filler is 1 wt % or more and 10 wt % or less, The proportion of the particulate filler in the filler is 50 wt % or more and 70 wt % or less.
6. The composite resin composition according to claim 5, wherein In the fibrous filler, only the ends of the fibrous filler in the fiber length direction are defibrated, The concentration of the low molecular weight resin around the end of the fibrous filler is greater than the concentration of the low molecular weight resin around the center of the fibrous filler in the fiber length direction.
7. The composite resin composition according to claim 1, wherein The filler is a natural material comprising cellulose.
8. The composite resin composition according to claim 1, wherein The main resin is an olefin resin. 9 . A composite resin molded body comprising the composite resin composition according to claim 1 .
